Solar or diesel: A comparison of costs for groundwater‐fed irrigation in Sub‐Saharan Africa under two energy solutions - Xie, Hua; Ringler, Claudia; Mondal, Md. A. H. (American Geophysical Union, 2021)
Sub-Saharan Africa has long been beset with food insecurity and energy poverty. Expanding irrigated agriculture can help boost food production in the region, but this requires energy for accessing water, especially in groundwater-fed irrigation. This paper compared economic performance of groundwater pumping for irrigation under two energy solutions: solar photovoltaic (PV) and diesel fuel. We estimated the life-cycle costs of the power units of two pumping systems for a range of crop and irrigation method scenarios and mapped their relative cost-effectiveness over cropland in sub-Saharan Africa. As a renewable and clean energy source, solar energy has attracted much attention and there is keen interest in investing in solar PV to support the development of irrigated agriculture. Results of this study provide insights into the prospects of promoting solar irrigation in sub-Saharan Africa.